Fekete-Szegö Functional for Bi-univalent Functions Related with Gegenbauer Polynomials - Ibrar Ahmad; Syed Ghoos Ali Shah; Saqib Hussain; Maslina Darus; Babar Ahmad (Journal of Mathematics)
In this paper, we introduce and investigate a new subclass of bi-univalent functions related with generating function of Gegenbauer polynomials. We will mainly find bounds on Maclaurin series coefficients for functions belonging to this class. We also study the famous Fekete-Szegö type problem for this subclass which is obtained. We will also point out many special cases as corollaries.